Indications and outcome associated with positive‐pressure ventilation in dogs and cats: 127 cases. Issue 3 (19th January 2022) - Cagle, Laura A.; Hopper, Kate; Epstein, Steven E.
Abstract: Objectives: To determine the indications and outcomes of positive‐pressure ventilation (PPV) and identify factors associated with successful weaning. Design: Retrospective study from October 2009 to September 2013. Setting: University teaching hospital. Animals: One hundred and eleven dogs and 16 cats. Measurements and Main Results: Medical records were retrospectively reviewed; signalment, indication for PPV, patient characteristics, blood gas, and ventilator variables during PPV, duration of PPV, and outcome were recorded. Dogs were most commonly ventilated for pneumonia (36/111; 32%) and cats for multiple pulmonary diseases (8/16; 50%). The median duration of PPV for all animals was 25.7 h (range, 0.1–957 h). Long‐term PPV (≥24 h) was performed in 53% of cases. No differences were noted in successful weaning rates between cases ventilated for pulmonary etiologies (23/99; 23%) versus nonpulmonary etiologies (9/28; 32%). Overall, 32 of 127 (25%; 30 dogs, 2 cats) animals were successfully weaned from PPV and 28 of 127 (22%; 26 dogs, 2 cats) survived to hospital discharge. Long‐term ventilation had a higher likelihood of successful weaning (26/67 [39%] vs 6/60 [10%], P = 0.0002) and higher rates of survival to discharge (23/67 [34%] vs 5/60 [8%], P = 0.0005) than short‐term ventilation. Animals with higher Pao 2 /Fio 2 and Spo 2 /Fio 2 and lower APPLE and SOFA scores on day 1 of PPV were more likely to be weaned ( P < 0.03). Conclusions: The outcome of PPV appears to be most heavily determined by the underlying disease process and no clear improvement in outcome could be demonstrated in this study, despite advances in veterinary critical care and ventilator management strategies since previous studies. Dogs and cats receiving PPV for more than 24 h in this study had a higher likelihood of a positive outcome. Several indices of oxygenation and illness severity at the onset of PPV were predictive of outcome and maybe useful when considering prognosis of these cases.